Progressive postoperative atrophy of ipsilateral thalamus, putamen, and globus pallidus in patients with temporal lobe epilepsy: A volumetric analysis - Aleksa Pejovic; Zorica Jokovic; Matthias Koepp; Marko Dakovic; Vladimir Bascarevic; Marija Jovanovic; Nikola Vojvodic; Dragoslav Sokic; Aleksandar J. Ristic (Epilepsia Open)
Abstract Objective Cortical atrophy close to medial temporal structures has been described consistently in patients with temporal lobe epilepsy (TLE). Successful TLE surgery may have a neuroprotective effect preventing further atrophy of temporal and extratemporal cortex. However, the effects of epilepsy surgery on subcortical structures demand additional enlightenment. This work aimed to determine how epilepsy surgery affects volumes of subcortical structures in medically refractory temporal lobe epilepsy patients. Methods We compared MRI volumes of subcortical structures in 62 patients with TLE (36 left, 26 right) before and after anterior temporal lobectomy with 38 TLE patients (20 left, 18 right) who were considered to be good surgical candidates and had at least two brain MRIs. Results There were no volume differences in subcortical structures on preoperative and initial MRIs of non‐operated TLE patients. At baseline, the ipsilateral thalamus and putamen in TLE patients were marginally smaller than contralateral structures. Operated patients showed a significant postoperative volume reduction in ipsilateral thalamus, putamen, and globus pallidus. In contrast, there were no significant volumetric reductions in non‐operated patients longitudinally. There were no volumetric changes associated with different surgical outcomes or different postoperative cognitive outcomes. Significance Our study demonstrated postoperative volume loss of thalamus, putamen and globus pallidus ipsilaterally to the side of resection. Our findings suggest surgery‐related changes, likely Wallerian degeneration within subcortical networks not related to seizure or cognitive outcome. Plain Language Summary We studied 100 patients with epilepsy, comparing those who had surgery to those who did not. After surgery, the thalamus, putamen and globus pallidus on the same side as the surgery shrank significantly, but not in non‐surgery patients. This suggests surgery‐related changes in deeper brain structures, unrelated to seizure freedom or cognitive outcomes. This research sheds additional light on the response of the subcortical structure to epilepsy surgery, highlighting potential areas for further study.